Presumed Primary Bacterial Rhinosinusitis-Associated Optic Neuritis in a Cat - Moghaddam, Rachael; Jaffey, Jared A.; Hostnik, Eric T.; Brower, Alexandra; Wycislo, Kathryn L. (Frontiers in Veterinary Science, 2020)
Acute bacterial rhinosinusitis is a common illness in children and can lead to complications such as preseptal/orbital cellulitis, orbital/subdural/cerebral abscessation, osteomyelitis, meningitis, and optic neuritis with blindness. Primary bacterial infections leading to rhinosinusitis in cats is rare and descriptive reports are lacking. The current report describes a cat with Escherichia coli and Actinomyces spp. infections causing severe chronic rhinosinusitis and subsequent loss of vision. Treatment with antibiotics and prednisolone coincided with a complete resolution of nasal disease-related clinical signs and substantial improvement in vision. This is the first description of a cat with presumed severe primary bacterial rhinosinusitis resulting in optic neuritis and loss of vision.